SCHOOL ASSESSMENT: THE MIDDLE WAY - Bulcock, Jeffrey W. (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 1982)
As any part of the human race falters in faith in the point of its own existence, so do the prospects of the institutions charged with supervising its self-renewal. Yet as Bulcock points out, if only to secure the immediate future to which the race is already committed - up to about the year 2040 - the schools of Western society have an immediate and challenging task: to make the most of our numerically dwindling younger generations. We are in a state of astonishing ignorance about the effectiveness of those institutions - our schools - that should meet this new challenge, namely to provide the minority work-force of a different society that is already on the way. He discusses the reasons why we at present maintain and indeed protect that state of ignorance, and offers examples of the means, already available to us, to overcome it. RÉSUMÉ Quand une partie quelconque de la race humaine n'a plus foi dans sa propre existence, il en va de même des institutions chargées d'assurer son renouvellement. Pourtant, comme le souligne Bulcock, ne serait-ce que pour assurer l'avenir immédiat de notre race (soit, jusqu'à environ l'an 2040), les écoles de nos sociétés occidentales ont une responsabilité immédiate et urgente: elles doivent en effet tirer le meilleur parti possible de nos jeunes générations dont les effectifs ne cessent de baisser. Nous ignorons à peu près tout de l'efficacité de ces institutions (nos écoles) qui doivent relever ce nouveau défi, à savoir de former la population active minoritaire d'une société diff érente qui s'annonce. Bulcock discute des raisons pour lesquelles nous tenons à maintenir et m~me à protéger cet état d'ignorance et il offre des exemples des moyens dont nous disposons pour y remédier.